Towards the Development of Telecare Business Model- Service Design Approach - Chuang Li-Min , Yang, Chung-Ho,Tseng Chia-Wei (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Aging society became a mutual issue across the world in recent years, many developed countries attempted to ease relevant social problems and reduce tremendous medical cost through telecare service model. Taking telecare managers, providers and demanders as samples, this research conducted analysis through business model blueprint and AHP after determining key factors of telecare service. The main purposes are: 1) Determining the key factors for telecare service through business model blueprint, 2) Defining customer’s need through AHP and 3) Providing customer’s need to telecare service practitioners as reference for service innovation model. Comprehensively, the most significant customer needs are ranked in order: ―emergency help service‖, ―in-time sensory warning response‖, ―solitary or people with disability‖, ―living in remote areas‖ and ―reduce overall patient time‖ through the results of this research, as reference for relevant practitioners.